Effects of reverse headgear on pharyngeal airway in patients with different vertical craniofacial features - Burcu BALOŞ TUNCER; Çağrı ULUSOY; Cumhur TUNCER; Çağrı TÜRKÖZ; Selin KALE VARLIK (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to investigate the effects of reverse headgear (RH) on pharyngeal airway morphology in two groups of Class III patients with different vertical craniofacial features in comparison with an untreated Class III group. Seventeen subjects (9 males, 8 females; mean age 11.3 ± 0.98 years) with optimum vertical growth and 17 subjects (10 males, 7 females, mean age 11.5 ± 1.1 years) with a vertical growth pattern treated with a removable intra-oral appliance and a Delaire type facemask were included. An untreated Class III control group of 11 subjects (8 males, 3 females, mean age 9.1 ± 1.1 years) was included to compare the treated groups. The paired t-test for intragroup and one-way ANOVA for intergroup comparisons were performed. The relationships between changes in the craniofacial morphology and airway were assessed by Spearman correlation analysis. The airway dimensions at the adenoid side and soft palate were increased in the treatment groups compared to the control group (p < 0.05). The nasopharyngeal area demonstrated a significant difference in normodivergent and control subjects (p < 0.05). No significant difference was found in the airway morphology due to different vertical features. The effect of RH treatment on the sagittal airway dimensions revealed no significant difference between different vertical craniofacial features in the short term.